The teacher: The central pivot of change and innovation - Grant, D. R. B. (Bernard Van Leer Foundation, 1974)
This paper stresses the importance of human factors in the adoption of innovations and exemplifies the teacher role in the case of preprimary programmes in the Caribbean. It presents various definitions of innovation, and analyses the resistance to its implementation and the time lag affecting dissemination. The success of innovative practices implies involvement of all concerned and a specification of the prime target of change: educational objectives, provision of equal opportunities, emphasis on rehabilitation, compensation, or development. One has to promote new teacher attitudes through an adequate professional preparation, extended role of supervisors, and inservice training. Parent participation must be enhanced in order to develop cultural experiences for children at home, and school community relationship has to be strengthened. Teachers must attain self-confidence and adopt new teaching styles involving a high interaction rate with the pupils. The final success is not a matter of expenditure but creativeness
Keywords: Early childhood care and education